2004
DOI: 10.4148/2378-5977.1615
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolites of receiving heifers and the relationship between bovine respiratory disease, weight gain, and carcass characteristics (2004)

Abstract: Plasma metabolites of receiving heifers and the relationship between bovine respiratory disease, weight gain, and carcass characteristics AbstractSix hundred sixty-five crossbred beef heifers initially weighing 495 lb were used to evaluate rectal temperature and plasma glucose, lactate, and urea nitrogen at initial processing as indicators of health status of newly arrived receiving cattle. We also evaluated the relationship between bovine respiratory disease (BRD), weight gain, and carcass characteristics. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…The observation of decreased yield grade and adjusted fat thickness measurements in the current study confirms previous studies reporting similar results as a result of BRD incidence (Gardner et al, 1999;Montgomery et al, 2008). Gardner et al (1999) found that Charolais steers affected with BRD at least once during the growing and finishing period were leaner than unaffected steers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The observation of decreased yield grade and adjusted fat thickness measurements in the current study confirms previous studies reporting similar results as a result of BRD incidence (Gardner et al, 1999;Montgomery et al, 2008). Gardner et al (1999) found that Charolais steers affected with BRD at least once during the growing and finishing period were leaner than unaffected steers.…”
Section: Discussionsupporting
confidence: 90%
“…Gardner et al (1999) found that Charolais steers affected with BRD at least once during the growing and finishing period were leaner than unaffected steers. Montgomery et al (2008), using commercial heifers obtained from commercial sale barns, found that animals requiring at least 1 treatment for BRD were leaner than unaffected heifers. Furthermore, fat thickness measurements declined with each subsequent treatment (Montgomery et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the carcasses of treated steers had lower fat content than the carcasses of healthy steers, which corroborates the findings of Garcia et al (), Gardner et al (), Montgomery et al () and Snowder et al (). Gardner et al (), who analyzed Charolais steers, and Montgomery et al (), who investigated heifers, found that animals treated for pneumonia at least once during rearing and fattening were characterized by lower fat deposition than healthy animals. Montgomery et al () also demonstrated that fat thickness decreased with an increasing number of treatments.…”
Section: Discussionsupporting
confidence: 93%
“…Gardner et al (1999), who analyzed Charolais steers, and Montgomery et al (2008), who investigated heifers, found that animals treated for pneumonia at least once during rearing and fattening were characterized by lower fat deposition than healthy animals. Montgomery et al (2008) also demonstrated that fat thickness decreased with an increasing number of treatments. In our experiment the lowest fatness occurred in carcasses of animals with lung diseases.…”
Section: Discussionmentioning
confidence: 99%